Toxicity assessment of a comercial Bacillus thuringiensis-based insecticide on Nile tilápia, Oreochromis niloticus (Research, Society and Development, 2021)
Biopesticides are used as an alternative to synthetic chemical pesticides application. Formulations based on Bacillus thuringiensis (Bt) spores are widely used, however, little is known about their effects on aquatic biota. The aim of the study was to evaluate the genotoxic and histopathological effects of a sublethal concentration of a commercial Bt-based biopesticide on Oreochromis niloticus. The fish were divided (n = 10) into a control group (CG) and an exposed group (GBt) at a concentration of 60 mg L-1 of the biopesticide Dipel® WP for 48 hours. After exposure, blood, gill, liver and kidney samples were collected for analysis of toxicity biomarkers. The results demonstrate that an acute exposure to Bt induces the increase of erythrocyte nuclei with segmented morphology. No micronucleus induction was observed. Histopathological analysis showed that within 48 hours of exposure, in GBt, there was a decrease in the frequency of hypertrophied hepatocytes. However, the biopesticide did not compromise tissue morphology in acute toxicity. Pesticides in general are constantly applied and usage regulations are not widely followed, our results suggest that sublethal concentrations can induce effects when exposed acutely. Biopesticides based on Bt in low concentrations appear to be less toxic to fish.